FRI0277 EFFECTIVENESS OF BDMARDS IN AS AND NR-AXSPA PATIENT POPULATIONS: EXPERIENCE FROM THE CORRONA REGISTRY. (2nd June 2020) - Hunter, T.; Blachley, T.; Malatestinic, W.; Harrold, L.; Dube, B.; Glynn, M.; Lisse, J.; Bolce, R.; Mease, P. J.
Abstract : Background: Axial spondyloarthritis (axSpA) consists of ankylosing spondylitis (AS), also referred to as radiographic axSpA (r-axSpA) and non-radiographic axSpA (nr-axSpA). AxSpA can lead to reduced mobility, pain, fatigue, and impact quality of life. While bDMARDs are available for treatment, the literature lacks studies exploring their real-world effectiveness in clinical registry patients with axSpA. Objectives: To describe patient characteristics of bDMARD initiators among the AS and nr-axSpA populations and the effectiveness of bDMARDs at the 6-month (± 3) post-initiation follow-up (FU) visit in the Corrona PsA/SpA Registry. Methods: This study included patients aged ≥ 18 years with AS per modified NY criteria and nr-axSpA per ASAS criteria enrolled between 3/2013 and 9/2019. Concurrently diagnosed patients with PsA were excluded. Baseline characteristics, such as demographic, clinical, disease activity, treatment, and patient-reported outcomes (PRO), were collected for those initiating a bDMARD at enrollment or during FU; response rates and mean change in disease activity and PRO between initiation and 6-month FU were calculated. Results: The AS (n=179) and nr-axSpA (n=32) bDMARD initiators groups were similar at initiation for mean age (AS: 49.1 yrs, nr-axSpA: 48.9 yrs), ASDAS scores (AS: 2.9, nr-axSpA: 2.8) and patient global assessment (AS: 59.6, nr-axSpA: 60.0). The two groups were different for time from disease duration (AS 8.5 yrs, nr-axSpA, 6.6 yrs), current NSAID use (AS: 64.2%, nr-axSpA: 46.9%) and naivete to cDMARDS (AS: 70.4%, nr-axSpA: 40.6%), TNFs (AS: 47.5%, nr-axSpA: 21.9%), non-TNFs (AS: 96.1%, nr-axSpA: 93.8%) and bDMARDs (AS: 46.9%, nr-axSpA: 21.9%). Patients were similarly impacted by their condition for BASDAI (AS: 5.0, nr-axSpA, 5.6), pain (AS: 55.8, nr-axSpA, 60.8) and fatigue (AS: 51.6, nr-axSpA, 59.9), but there was an imbalance in tender joint count (AS: 2.6, nr-axSpA, 13.4). At 6-month FU, both populations experienced minimal or no change in ASDAS scores (AS: -0.3, nr-axSpA: 0.0) remaining in a high state of disease activity (ASDAS, ≥2.2). A small percent of both groups achieved ASAS20 (AS: 20.1%; nr-axSpA: 21.9%) and ASAS40 (AS: 14 %, nr-axSpA: 15.6%). Further, bDMARD initiators had minimal decreases in BASDAI (AS: -0.6, nr-axSpA: -0.8), pain (AS: -8.5, nr-axSpA: -12.2), and fatigue (AS: -5.0, nr-axSpA: -7.9) scores. Conclusion: AS and nr-axSpA bDMARD initiators had a modest improvement in outcomes at six months. Twenty percent or fewer patients achieved ASAS20 or ASAS40, with many having residual impairment based on ASDAS, BASDAI, pain, and fatigue outcomes at six months. While patients are initiating biologic agents, room for improvement exists as many are not achieving optimal treatment response of inactive (ASDAS, <1.3) or low disease activity (ASDAS, <2.1). Disclosure of Interests: Theresa Hunter Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Taylor Blachley Employee of: Corrona, LLC, William Malatestinic Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Leslie Harrold Shareholder of: Corrona, LLC – shareholder, Grant/research support from: Pfizer – grant/research support, Consultant of: AbbVie, BMS, Roche – consultant, Employee of: Corrona, LLC – employment, Blessing Dube Employee of: Corrona, LLC, Meghan Glynn Shareholder of: Corrona, LLC – shareholder, Grant/research support from: Pfizer – grant/research support, Employee of: Corrona, LLC – employment, Jeffrey Lisse Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Rebecca Bolce Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau